Closure of subarterial ventricular septal defect with minimally invasive surgical technique: A case report - Duong, Duc Hung (Int J Surg Case Rep, 2019)
INTRODUCTION: Minimally invasive cardiac surgery has been applied for the treatment of ventricular septal defect (VSD) with various approaches. However, closure of subarterial VSD with minimally invasive technique via left parasternal thoracotomy is rarely reported. CASE PRESENTATION: A 22-year-old man, weighing 65 kg, with a diagnosis of subarterial VSD underwent successful repair with minimally invasive technique via left parasternal thoracotomy through third intercostal space. The peripheral perfusion was performed with femoral arterial and venous cannulation. Myocardium was protected by warm blood cardioplegia injected directly into aortic root by a long needle and aortic clamp introduced through the thoracotomy incision. DISCUSSION: The left parasternal thoracotomy through third intercostal space (ICS) allows to expose both the subarterial VSD and ascending aorta. Myocardial protection and repair of this defect can be performed merely without requirements of video assistance or unique instruments. The patient recovered rapidly and was satisfied with the cosmetic result. The primary concern of this technique is mammary tissue which can be injured by a transverse incision in female patients. In this case, we can transform into the longitudinal incision. CONCLUSION: This minimally invasive technique is feasible for the surgical treatment of subarterial VSD. Long-term follow-up and additional cases will be needed for validation of the safety and efficacy of this approach.